Equity valuation : MTU Aero Engines AG - Schaible, Lars (2017)
The goal of the report is to identify the fair equity value of the MDAX listed company MTU Aero Engines AG, which operates in the aircraft engine manufacturing industry. The work begins by reviewing the academic literature on investment valuation. Afterwards, the company’s business and financial performance is introduced and an overview of the aircraft engine supplying industry is given. The company divides into the segments Commercial OEM, MRO and Military OEM. Furthermore, the industry is characterized by high technological expertise and regulatory standards. In the next step, the share price is calculated based on the APV method and supported by a relative valuation. Even though, the multiples in the relative valuation suggest a lower share price, the APV result should reflect the fair value more accurately, since the multiples vary a lot across peer group companies. The report concludes with a sensitivity analysis of the results and the investment is recommended to be overweighed. The valuation results in a share price of €131.78, which represents a premium of 8.8% to the actual closing price of €121.10, as of May 17, 2017. Over the explicit forecast period revenues grow at 6.6% CAGR and FCFF at 4.2%. The fair value of the report is almost equal to the one from the reference report by Barclays Bank PLC, which valued MTU’s shares at €133.00 as of April 28, 2017.